Revealing phosphoproteins playing role in tobacco pollen activated in vitro - Fíla, Jan; Matros, Andrea; Radau, Sonja; Zahedi, René Peiman; Capková, Věra; Mock, Hans-Peter; Honys, David (Proteomics, 2012)
The transition between the quiescent mature and the metabolically active germinating pollen grain most probably involves changes in protein phosphorylation status, since phosphorylation has been implicated in the regulation of many cellular processes. Given that, only a minor proportion of cellular proteins are phosphorylated at any one time, and that phosphorylated and nonphosphorylated forms of many proteins can co-exist within a cell, the identification of phosphoproteins requires some prior enrichment from a crude protein extract. Here, we have used metal oxide/hydroxide affinity chromatography (MOAC) based on an aluminum hydroxide matrix for this purpose, and have generated a population of phosphoprotein candidates from both mature and in vitro activated tobacco pollen grains. Both electrophoretic and nonelectrophoretic methods, allied to MS, were applied to these extracts to identify a set of 139 phosphoprotein candidates. In vitro phosphorylation was also used to validate the spectrum of phosphoprotein candidates obtained by the MOAC phosphoprotein enrichment. Since only one phosphorylation site was detected by the above approach, titanium dioxide phosphopeptide enrichment of trypsinized mature pollen crude extract was performed as well. It resulted in a detection of additional 51 phosphorylation sites giving a total of 52 identified phosphosites in this set of 139 phosphoprotein candidates.
Keywords: fosforylace; proteom; titan; 2D gelová elektroforéza; Titanium; Phosphorylation; molekulární sekvence - údaje; Amino Acid Sequence; Electrophoresis, Gel, Two-Dimensional; fosfoproteiny; Sequence Alignment; pyl; sekvenční seřazení; elektroforéza v polyakrylamidovém gelu; Phosphoproteins; Plant Proteins; chromatografie afinitní; Pollen; Electrophoresis, Polyacrylamide Gel; Nicotiana; sekvence aminokyselin; Molecular Sequence Data; Proteome; Chromatography, Affinity; tabák; rostlinné proteiny